Revitalization of The Mapogau Hanua Traditional Service as a Refillation of Character Education Values in Geographic Learning - Syarif, Erman (Universitas Negeri Makassar, 2021)
The aims of this study are: 1) to identify the values contained in the Mappogau Hanua traditional ceremony, 2) To determine the position of the Mapogau Hanua traditional ceremony as a reflection of character building in geography learning. This type of research is qualitative with a case study approach. The collection technique was carried out by observation, interviews, documentation, and literature review regarding the Mapogau Hanua traditional ceremony. Data analysis through data reduction, data presentation and conclusion drawing. The results showed: 1) the values contained in the Mappogau Hanua traditional ceremony, namely the value of obedience, the value of local knowledge, the value of solidarity, the value of religion/belief, the value of nature conservation, and aesthetic value, and 2) the values of the traditional Mapogau ceremony. Hanua is important to be instilled in students at the level of formal education, especially in high school which aims to shape character. To realize the implementation of character education in schools, all components must be involved, namely: curriculum content, learning and assessment processes, handling or management of subjects, school management, classroom management, implementation of co-curricular activities or activities, extracurricular activities, empowerment infrastructure, financing, and work ethic for all school residents and the surrounding environment, both the school environment and the home environment